2016
DOI: 10.1038/ng.3650
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding somatic and inherited single-nucleotide variants converge to promote ESR1 expression in breast cancer

Abstract: Sustained expression of the oestrogen receptor alpha (ESR1) drives two-thirds of breast cancer and defines the ESR1-positive subtype. ESR1 engages enhancers upon oestrogen stimulation to establish an oncogenic expression program1. Somatic copy number alterations involving the ESR1 gene occur in approximately 1% of ESR1-positive breast cancers2–5, implying that other mechanisms underlie the persistent expression of ESR1. We report the significant enrichment of somatic mutations within the set of regulatory elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 58 publications
(90 reference statements)
4
98
0
Order By: Relevance
“…Since our hypothesis was that noncoding somatic mutations might activate transcriptional regulatory programs from heterologous cell types, we predicted that functional noncoding mutations in regulatory elements should result in gain-of-function genetic events [60]. Such events may be evident as gain-of-binding site motifs for transcriptional trans-activators.…”
Section: Resultsmentioning
confidence: 99%
“…Since our hypothesis was that noncoding somatic mutations might activate transcriptional regulatory programs from heterologous cell types, we predicted that functional noncoding mutations in regulatory elements should result in gain-of-function genetic events [60]. Such events may be evident as gain-of-binding site motifs for transcriptional trans-activators.…”
Section: Resultsmentioning
confidence: 99%
“…For example, because multiple enhancers can regulate a gene, a mutation in any one of the enhancers could disrupt TF binding and cause a slight change in gene expression (Figure 1B). Bailey et al identified the set of regulatory elements targeting ESR1 in breast cancer and found that collectively, these elements contain a significant enrichment of mutations [32]. All of the somatic non-coding mutations are predicted to modulate binding of ESR1 regulators and furthermore, the majority of those tested showed a significant effect on ESR1 gene expression [32].…”
Section: Non-coding Drivers In Cancermentioning
confidence: 99%
“…Bailey et al identified the set of regulatory elements targeting ESR1 in breast cancer and found that collectively, these elements contain a significant enrichment of mutations [32]. All of the somatic non-coding mutations are predicted to modulate binding of ESR1 regulators and furthermore, the majority of those tested showed a significant effect on ESR1 gene expression [32]. Thus, the authors speculate that non-coding drivers may be characterized by selection acting on a phenotypic outcome (e.g.…”
Section: Non-coding Drivers In Cancermentioning
confidence: 99%
See 2 more Smart Citations